38: Blood Lead, Cadmium and Mercury Levels in Children Receiving Primary Healthcare in Toronto: A Collaborative Study. Issue 6 (1st June 2014) - Peterson, E; Birken, CS; Parkin, PC; Chen, Y; Archibold, J; Stover, A; Copes, R; Maguire, JL
Abstract: BACKGROUND: There is limited Canadian data on blood lead, cadmium and mercury levels in early childhood, a population that is highly vulnerable to the effects of these metals. Mercury and lead exposures have been linked to neurological effects and cadmium exposures have been linked to kidney and bone damage. Identifying subpopulations with higher levels and the assoicated risk factors is important for directing future clinical and public health intiatives in this age group of Ontario chidren. OBJECTIVES: To build capacity within the public health and primary healthcare sectors, collaboration between Public Health and a primary care research network for children was formed to study blood lead, cadmium and mercury levels in children <6 years of age receiving routine primary healthcare. DESIGN/METHODS: Children younger than five years of age receiving routine primary healthcare were recruited through this primary-care research network of family physicians, pediatricians, researchers and policy makers. Risk factors for heavy metal exposure were collected through a series of standardized questionnaires administered to the participant's parents. In addition, a small blood sample was obtained from each child and tested for lead, mercury and cadmium. RESULTS: Preliminary heavy metal data was available for 205 children. Mean age was 42 months and 52% of participants were male. 70% of children were Caucasian and 30% were visible minorities. Eighty-five percent of the participants had a household income >$60, 000. Geometric mean concentrations of lead, mercury and cadmium were 0.67 μg/dL (95% CI 0.63 μg/dL to 0.73 μg/dL), 0.59 μg/L (95% CI 0.45 μg/L to 0.55 μg/L) and 0.11 μg/L (95% CI 0.11 μg/L to 0.12 μg/L), respectively. Two children had mercury levels above the Health Canada methylmercury guidance of 8 μg/L. No child had abnormal lead or cadmium levels. CONCLUSIONS: Through a multidisciplinary collaboration, we have demonstrated that heavy metal exposure can be measured in early childhood during routine primary healthcare. In this preliminary study, two children were identified with elevated mercury blood levels. These findings should be interpreted with caution until a larger, more diverse, population of children is studied.